DOA Estimation in Dynamic Environment using DMUSIC & DPM Algorithms - Khumane, DD; Jagade, SM (International Journal of Computer Sciences and Engineering, 2019)
Smart antenna can be reducing multipath and co-channel interference. These benefits include the enhancement of coverage and the channel capacity, lower transmitted power, better signal quality, higher data rate and providing value-added services such as users position location (PL) for dynamic condition. This paper deals with the performance evaluation of Dynamic-MUSIC & Dynamic-PM algorithm for Direction of Arrival (DOA) estimation for smart antenna system using eigenvalue decomposition and without eigen decomposition based algorithms respectively. We focus on the dynamic environment of user i.e. user moves from his initial position to particular location. And by using DMUSIC & DPM estimate their correct position location (PL) to provide the services to the desired user using extended version of MUSIC & PM.